"Russia Accuses Fleet Street": Journalists and MI6 during the Cold War. (April 2015) - Dorril, Stephen
An interesting but under-researched area of journalism studies is the relationship between journalists, particularly foreign correspondents, and the intelligence services during the cold war. The aim of this paper is to consider whether there is any evidence to back up specific allegations made in the Soviet era press in December 1968 that in the post–Second World War period named leading British journalists working for the national newspapers had a covert relationship with the British Secret Intelligence Service that involved their recruitment as agents and the use of intelligence-derived material in their articles in the press. The paper raises questions about the methods of researching such alleged activities. Is it possible in the absence of files from the secret intelligence services to undertake a serious study of such activities? Does the development of digital sources and archives open new fields of detailed study? It also reveals the potential historical significance of the role journalists played in the reporting of key events and policy issues during the cold war.